Pengaruh metode pembelajaran CTL terhadap hasil belajar IPA siswa kelas VIII ditinjau dari kemampuan berkomunikasi - Bayu Hatmokomukti Wiyono; Widodo Budhi (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2018)
The aim of this research was to find out the impact of using CTL method toward the students’ learning achievement in the science of grade VIII reviewed from communication ability. The object of this research was the students’ learning achievement in a science subject. This type of the research is quasi-experiment. The techniques of collecting the data are using test, questioner, and documentation. The instrument test is multiple choice; consist of  40 questions and questioner consist of 30 statements. As the result, the researcher obtained f calculate = 5,962 with p = 0,016, the average of learning result is 28,37, the average of the questioner is 75,03. based on the average of the learning achievement and questioner, there is an impact of using CTL method toward the students’ learning achievement in the science of grade VIII reviewed from communication ability.